Life After Extinction: The participatory performances of Robyne Latham. (3rd April 2018) - Stevens, Lara
Abstract : Thinking about the value of human survival in the age of the Anthropocene this article asks: What about art that is created by people who have already lived for generations with the possibility of having to abandon the fantasy of their endurance, not of their species, but of their race and culture? What about performances and visual artworks that are created by Indigenous people who live with the legacy of genocide, with a recent history in which the extinction of their race was a very real possibility? How does this kind of art stage what is non-present, that which has perhaps already been lost, but also that which endures? This article considers these questions through the performance The Aborigine Is Present (2015), conceived of and performed (with others) by Australian artist Robyne Latham, Latham's sculptural installation Empty Coolamons (2014), and the performance Remembering the Empty Coolamons (2017). I argue that works like Latham's teach us that we don't have to abandon hope for the endurance of our species, that we can remember or learn how to practice an ethics of care for each other and thereby reconfigure colonialist attitudes and ignorance that will make our place in the biosphere constructive and even vital to non-human others.